ANALISIS SISTEM INFORMASI MANAJEMEN PERSEDIAAN BARANG: STUDI KASUS PADA UMKM NASI KEBULI - Pilyadi, Windika; Auliana, Sigit; Aryono, Gagah Dwikiputra (Information Technology Education Department, 2025)
Inventory management is a crucial aspect in supporting the sustainability and operational efficiency of Micro, Small and Medium Enterprises (MSMEs). This study aims to analyze the implementation and effectiveness of inventory management information systems in Nasi Kebuli MSMEs. A qualitative case study approach was used with data collection through interviews, direct observation, and document analysis to evaluate how the system used supports stock tracking, inventory control, and decision making. The results show that the existing system helps simplify the inventory process and reduce manual errors, but still has limitations in the aspects of integration, real-time data accuracy, and user accessibility. This research emphasizes the importance of adopting more reliable and user-friendly digital solutions to improve operational performance and support business growth. This study contributes to the literature related to the utilization of information systems in MSME environments and offers practical insights for digital transformation in small-scale food businesses.